Mobility, food and housing: responsibility, individual consumption and demand-side policies in European deep decarbonisation pathways - Moberg, Karen R.; Dorner, Florian (Energy efficiency, 2019)
The Brundtland Commission report ‘Our Common Future’ highlighted that residents in high-income countries lead lifestyles incompatible with planetary boundaries. Three decades later, consumption-related greenhouse gas (GHG) emissions have continued to increase. To achieve ‘well below 2°C’ and 1.5 °C goals, consumption-related emissions must be substantially reduced in the coming decades. This paper provides insights on how to pursue 1.5 °C pathways through changes in household consumption. It draws on original data gathered in the project ‘HOusehold Preferences for reducing greenhouse gas Emissions in four European High Income Countries’ (HOPE) to analyse policies targeting and affecting direct and indirect GHG emissions in three household consumption categories (mobility, housing and food) in four countries (France, Germany, Norway and Sweden) and four medium-sized cities. This paper demonstrates discrepancies and similarities between current governmental policy approaches in the four countries and household perceptions of consumption changes with respect to policy mechanisms, responsibilities and space for acting on mitigation. Current demand-side policy strategies rely heavily on instruments of self-governance and nudging behaviour. Whilst some of our data suggests that households broadly accept this, it also suggests that governments could more actively lead and steer demand-side mitigation via adjusting and supplementing a comprehensive list of 20 climate policy measures currently in place in one or more of the case countries. The paper concludes by suggesting areas for more effective policy change and household-level climate change mitigation to feed the next update of climate pledges under the Paris Agreement.